CHARACTERISTICS OF TYPE 3 NEOVASCULARIZATION LESIONS: Focus on the Incidence of Multifocal Lesions and the Distribution of Lesion Location. Issue 6 (June 2020) - Kim, Jae Hui; Chang, Young Suk; Kim, Jong Woo; Kim, Chul Gu; Lee, Dong Won
Abstract : Purpose: To evaluate the incidence of multifocal lesions and the distribution of lesion location in Type 3 neovascularization. Methods: This retrospective, observational study included 148 eyes of 148 patients diagnosed with Type 3 neovascularization. The number of Type 3 neovascularization lesions was counted, and the incidence of multiple lesions in an eye was estimated. In addition, the distance from the fovea to the lesion and the geographic location of the lesion were estimated. Pseudodrusen incidence was compared between eyes with and without multifocal lesions. Results: In total, 169 Type 3 neovascularization lesions were noted. A single lesion was noted in 130 eyes (87.8%), whereas 2 or 3 multifocal lesions were noted in the remaining 18 eyes (12.2%). The mean distance from the fovea to the lesion was 898.8 ± 324.9 µ m. The distribution of lesion locations exhibited a fovea-sparing pattern. No lesions were located within 200 µ m of the fovea, 20 lesions (11.8%) were located >200 and ⩽500 µ m away from the fovea, 89 lesions (52.7%) were located >500 and ⩽1, 000 µ m away from the fovea, and 60 lesions (35.5%) were located >1, 000 µ m away from the fovea. Pseudodrusen incidence was significantly higher in eyes with multifocal lesions ( P = 0.024). Conclusion: Two or more multifocal lesions were noted in 12.2% of eyes with Type 3 neovascularization, and pseudodrusen incidence was higher in eyes with multifocal lesions. In addition, lesion distribution exhibited a fovea-sparing pattern. These characteristics may be associated with the distinct pathophysiology of Type 3 neovascularization. Abstract : Multifocal lesions were noted in 12.2% of the eyes with Type 3 neovascularization. In addition, lesion distribution exhibited a fovea-sparing pattern. These characteristics may be associated with the distinct pathophysiology of Type 3 neovascularization.